Creating a Development Framework: a Generic Lens for Public Markets’ Analysis and Development in Integration With Their Zone of Influence Revitalization - Ahmed, Nourhan (AUC Knowledge Fountain, 2022)
This thesis discusses how the development of public markets through a structured framework can be a catalyst for revitalizing its zone of influence. Public markets have always been marked by their rich experience, and their central role in towns, cities, and villages, as they have been vital engines for urban growth and cities formation since their prevalence. Needless to mention their role in entrepreneurship and their significance for the social development of neighborhoods. Nowadays, local governments are rediscovering the central role of public markets and are putting them under focus to catalyze the urban growth and neighborhoods revitalization by their development. This role entails regenerating public spaces, developing buildings, and fostering healthy social interactions and local economic structures. Despite this interest, there has been limited scholarly attention given to the notion that developing public markets can be a tool to physically transform its surrounding zone of influence inside the city. Hence, this thesis contributes to filling in the gap by studying the realm of public markets and generating a development framework that can be used for analyzing and developing any market in integration with its zone of influence revitalization. This thesis used both secondary and primary research methods to study the active role of public markets in relation to their zone of influence and the different systems, functions, and components of public markets. It also used secondary research methods to study the different theories and approaches that can be used for analyzing and dissecting the public markets into their basic units and their relationships. By using the above methodology, the thesis created a development framework that can be used for analyzing any market and developing it in integration with its zone of influence revitalization. Then, it applied the development framework on a case study, Souq Al-Tunsi. The findings of this application revealed that the core problems that affect its functionality are: informality, lack of management, poor education, and having an informal culture. As part of developing the market in integration with its zone of influence revitalization, the thesis proposed guidelines such as: formalizing the market and its surrounding area, enhancing the education and culture, creating a market management body, and upgrading the market’s services, urban fabric, and built-up form in correspondence with its context. Applying these guidelines leads to a better selling process, efficient supply chain of goods, renovating historic monuments in the area of the market, provision of quality infrastructure and urban fabric systems, reviving landmarks, and creating active public spaces. Applying these guidelines also leads to increase the diversity, safety, and attractiveness of the market and its surrounding area, leading to an increase in the number of customers, the profitability of the market, and the upgrade of the whole area.